Sosialisasi dan demo pembuatan hand sanitizer bahan alami sebagai upaya peningkatan personal higiene masyarakat Desa Majannang, kecamatan Maros Baru - Herlinah B, Herlinah; Fadhli, Fadhli; Sajiah, Sajiah; Darti Akhsa, Amaliah Chintami (Patria Artha Journal of Community (PKM), 2021)
Majannang Village is a village located in the Maros Baru sub-district which has the status of a definitive village and is also classified as a self-employed village. Based on the results of the review, people's income in general comes from fish ponds, around 70%. Sources of clean water are very limited and are obtained from rain-fed wells. This is due to the low habit of washing hands in Majannang Village, which is 8.02%. In addition, 42.81% of residents consume bottled water. Discussion: 51% of respondents do not have access to sufficient clean water, thus reducing the habit of washing hands. One of the efforts to improve hand washing habits by means of pre-post tests and counseling, it can be seen that public knowledge about the benefits and ways of making hand sanitizers increased from 28% to 66%. Methods: The method of collecting data in this activity is to use a pre-post test design as a measure of knowledge. In addition, observations and questionnaires were distributed to obtain other supporting information. Then the data were analyzed using statistical analysis. Conclusion: The activity of making hand sanitizers from natural ingredients has a positive impact on residents regarding knowledge about the use of natural materials in the surrounding environment and increasing the potential for hand washing habits of residents.Keywords: Hand sanitizer, natural ingredients, hand washing, pre-post test